Invisible wounds: Community exposure to gun homicides and adolescents’ mental health and behavioral outcomes - Christine Leibbrand (SSM Popul Health, 2020)
Prior research has illustrated the importance of some types of local community crime for adolescents' outcomes. However, we have little knowledge about the extent to which gun homicides within adolescents' neighborhoods affect their mental health and behavioral outcomes. This is important because local gun homicide incidents may be uniquely harmful for adolescents and their association with adolescents' mental health and behavior may represent an underappreciated externality of the U.S.‘s gun violence epidemic. In this study, we used data on the geocoded location of gun homicides linked with restricted Fragile Families and Child Wellbeing Study data to examine whether gun homicides incidents near adolescents' homes and/or schools were associated with their mental health and behavioral outcomes. We found that the occurrence of a gun homicide near an adolescent's home or school was associated with significantly worse symptoms of anxiety and depression for girls and, in some cases, with symptoms of anxiety for boys. We further found that these relationships varied depending on the distance of gun homicide incidents to homes and schools.